Resistance of herbaceous cotton to Anthonomus grandis Boheman, 1843 (Coleoptera: Curculionidae) and interaction with insecticide - Soares, José Janduí; Lara, Fernando Mesquita (Pesquisa Agropecuaria Brasileira, 1993)
The experiment was carried out at Faculdade de Ciências Agrárias e Veterinárias - Campus de Jaboticabal - UNESP, São Paulo State, in 1990/1991, to verify the resistance of some herbaceous cotton genotypes (Gossypium hirsutum L.) to boll weevil, and the interaction of these genotypes with insecticide. The genotype La780-843FR showed the smallest percent values of square buds damage by the boll weevil and the best results in interaction with the insecticide.